Assessing Competencies in a Master of Science in Clinical Research Program: The Comprehensive Competency Review. Issue 6 (29th August 2015) - Robinson, Georgeanna F.W.B.; Moore, Charity G.; McTigue, Kathleen M.; Rubio, Doris M.; Kapoor, Wishwa N.
Abstract: Competencies in Master of Science Clinical Research programs are becoming increasingly common. However, students and programs can only benefit fully from competency‐based education if students' competence is formally assessed. Prior to a summative assessment, students must have at least one formative, formal assessment to be sure they are developing competence appropriate for their stage of training. This paper describes the comprehensive competency review (CCR), a milestone for MS students in Clinical Research at the University of Pittsburgh's Institute for Clinical Research Education. The CCR involves metacognitive reflection of the student's learning as a whole, written evidence of each competency, a narrative explaining the choice of evidence for demonstrating competencies, and a meeting in which two faculty members review the evidence and solicit further oral evidence of competence. CCRs allow for individualized feedback at the midpoint in degree programs, providing students with confidence that they will have the means and strategies to develop competence in all areas by the summative assessment of competence at their thesis defense. CCRs have also provided programmatic insight on the need for curricular revisions and additions. These benefits outweigh the time cost on the part of students and faculty in the CCR process.